Corporate Governance and Tax Avoidance: A Study on Indonesian Listed Companies (2016-2020) - Mar'atul 'Ainish Sholikhah; Fajar Nurdin (Institut Agama Islam Negeri Kendari, 2022)
This research objective is to find out the effect of independent commissioners, institutional ownership, managerial ownership, and audit committees on tax avoidance of service companies listed on the IDX in 2016-2020. This quantitative study uses multiple linear regression analysis as a hypothesis test. This study used secondary data from the financial statements of service companies listed on the IDX in 2016-2020. There are 28 samples of service companies listed on the IDX with a research period of 2016-2020, which were selected using the purposive sampling method used in this research. The results showed that the independent board of commissioners, institutional ownership, managerial ownership, and the audit committee had a significant positive effect on tax avoidance with a coefficient of determination of 40.1%. Thus, independent commissioners, institutional ownership, managerial ownership, and audit committees have an important role in tax planning, namely tax avoidance.